Tunable diode laser measurements of hydrothermal/volcanic CO2 and implications for the global CO2 budget - Pedone, M.; Aiuppa, A.; Giudice, G.; Grassa, F.; Francofonte, V.; Bergsson, B.; Ilyinskaya, E. (Copernicus Publications, 2014)
Quantifying the CO2 flux sustained by lowtemperature fumarolic fields in hydrothermal/volcanic environments has remained a challenge, to date. Here, we explored the potential of a commercial infrared tunable laser unit for quantifying such fumarolic volcanic/hydrothermal CO2 fluxes. Our field tests were conducted between April 2013 and March 2014 at Nea Kameni (Santorini, Greece), Hekla and Krýsuvík (Iceland) and Vulcano (Aeolian Islands, Italy). At these sites, the tunable laser was used to measure the path-integrated CO2 mixing ratios along cross sections of the fumaroles’ atmospheric plumes. By using a tomographic post-processing routine, we then obtained, for each manifestation, the contour maps of CO2 mixing ratios in the plumes and, from their integration, the CO2 fluxes. The calculated CO2 fluxes range from low (5.7 +/- 0.9 t d-1; Krýsuvík) to moderate (524 +/-108 t d-1; La Fossa crater, Vulcano). Overall, we suggest that the cumulative CO2 contribution from weakly degassing volcanoes in the hydrothermal stage of activity may be significant at the global scale. Published 1209–1221 2V. Dinamiche di unrest e scenari pre-eruttivi JCR Journal open